Heterogeneity in Expert Recommendations for Designing Carbon Pricing Policies across the Globe - Frikk Nesje; Robert C. Schmidt; Moritz A. Drupp (Center for Economic Studies and ifo Institute (CESifo), 2023)
Pricing the emissions of greenhouse gases is widely considered as key to tackling climate change. While carbon pricing schemes are proliferating, the vast majority of emissions is not yet covered. Designing carbon pricing policies requires navigating crucial design choices, such as addressing distributional and competitiveness concerns. Here, we present recommendations from a global survey of more than 400 experts to inform key design issues for carbon pricing policies. We find that almost twice as many experts favor a carbon tax over a cap-and-trade scheme for unilateral carbon pricing, and three-quarters strongly recommend using border carbon adjustment to address competitiveness concerns. Recommendations on the usage of revenues from carbon pricing exhibit a substantial degree of heterogeneity. While transfers to particularly affected households and equal lump sum transfers are among the options most favored, these account for only around 40 percent of recommendations. In terms of country and observable expert characteristics, we find that experts from countries with a higher GDP per capita recommend equal lump sum transfers to households more often, and that the clear preference for carbon taxes only exists in richer countries. While economists recommend lump-sum transfers to households and reducing distortionary taxes more often, non-economic experts rather recommend using revenue for governmental spending, such as on environmental public goods or renewable energy subsidies. Our results provide insights for science and policy to improve the design of unilateral carbon pricing policies.
Keywords: Q54; H23; 330; carbon pricing; expert survey; carbon tax versus emission trading; border carbon adjustment; revenue recycling